Rational and practical use of imaging in COVID-19 pneumonia - Sohail, Saba (Pak J Med Sci, 2020)
The severe form of the COVID-19 pandemic caused by the SARS-CoV-2 virus, has largely manifested as a predominant respiratory illness causing severe pneumonia characterized by bilateral, subpleural ground glass haze, progressing to consolidation, and fibrosis on imaging. There is some discrepancy between the governmental guidelines, professional Societies and Radiology and Respiratory Medicine specialists with divided opinions between the use of the chest X-rays and CT scan, and whether the use be screening or diagnostic. So far, the most balanced recommendations have been proposed by the Fleischner Society, which are endorsed by the Radiological Society of Pakistan as well. This writeup describes the approach for a rational use of imaging to the best advantage in the current situation according to local resources, and restricting the spread of infection. The most practical compromise for Pakistan appears to be the use of portable digital radiography equipment, and point-of- care ultrasound; with CT scan reserved for clinical situations not explained by the above two modalities, or demanding disease stratification.